Impact of Drought and Flooding on Alkaloid Production in Annona crassiflora Mart - Ana Beatriz Marques Honório; Iván De-la-Cruz-Chacón; Mariano Martínez-Vázquez; Magali Ribeiro da Silva; Felipe Girotto Campos; Bruna Cavinatti Martin; Gustavo Cabral da Silva; Carmen Sílvia Fernandes Boaro; Gisela Ferreira (Horticulturae, 2021)
The Brazilian Cerrado is the second largest Brazilian biome. In recent decades, a reduction in rainfall has indicated an extension of the dry season. Among the many native species of the Cerrado of the Annonaceae family and used in folk medicine, Annona crassiflora Mart. has fruits of high nutritional value and its by-products are sources of bioactive compounds, such as alkaloids. The aim of the study was to investigate how water stress impacts the production of alkaloids. The study was carried out in a nursery, and the knowledge was flood, field capacity and drought. Gas exchange, chlorophyll a fluorescence, antioxidant enzymes, total soluble sugars, starch, reducing sugars, sucrose, total alkaloids and liriodenine were analyzed. We observed that plants subjected to drought had an increase in the production of total alkaloids and liriodenine, without a reduction in photosynthetic metabolism. Plants kept under drought and flood conditions dissipated higher peroxidase activity, while catalase was higher in flooded plants. Starch showed the highest concentration in flooding plants without differing from drought plants; the lowest trehalose concentrations were found in both drought and flooding plants. The drought stimulated the synthesis of total alkaloids and liriodenine without reducing the primary metabolism, which suggests adaptation to Cerrado conditions.